2020
DOI: 10.1002/eng2.12235
|View full text |Cite
|
Sign up to set email alerts
|

Boosting effects of Spirulina platensis, whey protein, and probiotics on the growth of microflora and the nutritional value of ayran

Abstract: Great attention has been given to Spirulina platensis for consideration as the superfood of the future due to its high bioactive compounds and nutritional values. Boosting effects of S. platensis and whey protein hydrolysates (WPH) on the growth of probiotics in ayran, a fermented milk product, through the fermentation and storage periods were investigated in this study. This study aimed to enhance the growth of Lactobacillus delbrueckii subsp. bulgaricus, Bifidobacterium lactis, Streptococcus thermophilus, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…The analyzed studies were mainly focused on the production of novel dairy products, such as milk-based fermented beverages (Ayran, Labneh, fermented milks, acidophilus milks, milk kefir, yogurt, and probiotic yogurt) and different cheeses (probiotic Feta-type cheese, Kareish cheese, and Greek soft cheese), as well as lactose-free beverages, including soy yogurt and soy fermented beverages, vegan kefir, and water kefir ( Table 2 ). In detail, the studies on ayran [ 67 , 68 ] confirmed the positive influence of A. platensis incorporation on the growth and survival of Str. thermophilus , Lb.…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…The analyzed studies were mainly focused on the production of novel dairy products, such as milk-based fermented beverages (Ayran, Labneh, fermented milks, acidophilus milks, milk kefir, yogurt, and probiotic yogurt) and different cheeses (probiotic Feta-type cheese, Kareish cheese, and Greek soft cheese), as well as lactose-free beverages, including soy yogurt and soy fermented beverages, vegan kefir, and water kefir ( Table 2 ). In detail, the studies on ayran [ 67 , 68 ] confirmed the positive influence of A. platensis incorporation on the growth and survival of Str. thermophilus , Lb.…”
Section: Resultsmentioning
confidence: 97%
“…However, as also demonstrated for probiotic yogurt, while Spirulina promotes LAB growth, it may impair the rheological properties of the final product. For example, in Ayran, as well as in a probiotic yogurt, a decrease in viscosity with an increasing amount of Spirulina was observed, probably due to the high LAB load and titratable acidity level, which enhanced casein proteolysis [ 67 , 68 , 71 ]. Studies on Ayran enriched with Spirulina also showed that an algal concentration higher than 0.25% decreased taste and thickness scores [ 67 , 68 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Strains from olives were isolated on selective de Man, Rogosa, and Sharpe (MRS) media (Merck Millipore Germany, catalog # 110660) [ 34 , 35 ]. Isolations from chunks, brine, and minced fermented black and green olives were done on MRS media by the spread plate method [ 36 ]. Isolates were characterized by morphological, biochemical, and physiological characteristics.…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, a trend has begun to add microalgae (cyanobacterial biomass) in fermented milk products to increase the functional product properties by promoting the viability of probiotics and also to improve their nutritional properties (Varga et al 2002;Beheshtipour et al 2013). Spirulina is frequently used for human consumption in various forms: tablets, capsules, or food additives such as dairy products (Varga et al 2002;Guldas and Irkın 2010;Malik et al 2013;Agustini et al 2016;Barkallah et al 2017;Darwish 2017;Szmejda et al 2018;Çelekli et al 2019;Narayana and Kale 2019;Çelekli et al 2020;Bosnea et al 2021), gelatin desserts (Gouveia et al 2008), and bakery products (De Marco et al 2014;Ashoush and Samar 2019;Grahl et al 2020;Da Silva et al 2021).…”
Section: Introductionmentioning
confidence: 99%